2010
DOI: 10.1111/j.1439-0388.2010.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection based on progeny testing induces rapid changes in myostatin allele frequencies - a case study in sheep

Abstract: In this study we show that selection based on progeny testing is able to induce a rapid change in allele frequency, even when a fairly broad and balanced breeding goal is applied. The myostatin 3'-UTR mutation (c.*1232G>A) previously found to affect muscularity in Texel sheep is also present in the Norwegian White Sheep population. By genotyping the rams used for artificial insemination (born in1977-2006), a rapid increase in the c.*1232G>A allele frequency was observed, from 0.31 in 1990 to 0.82 in 2006. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The significant phenotypic effect of the GDF9 c.1111A - allele observed in this study could therefore indicate that this allele originate from Finnish landrace. The development in allele frequency in the AI rams population since 1990 also resemble the pattern observed for another imported allele, namely the Texel MSTN c.*1232A - allele [22]. In both cases a new breed has been imported to improve key traits, litter size and meatiness respectively, and after some latency the organized breeding system catches the causal allele and rapidly increase its frequency, first in the AI ram population and subsequently in the whole ewe population.…”
Section: Discussionmentioning
confidence: 74%
“…The significant phenotypic effect of the GDF9 c.1111A - allele observed in this study could therefore indicate that this allele originate from Finnish landrace. The development in allele frequency in the AI rams population since 1990 also resemble the pattern observed for another imported allele, namely the Texel MSTN c.*1232A - allele [22]. In both cases a new breed has been imported to improve key traits, litter size and meatiness respectively, and after some latency the organized breeding system catches the causal allele and rapidly increase its frequency, first in the AI ram population and subsequently in the whole ewe population.…”
Section: Discussionmentioning
confidence: 74%
“…Boman et al . () showed that selection based on progeny testing in the Norwegian White Sheep population favoring muscled carcasses indirectly induced a rapid frequency change of a causative mutation in the 3′‐untranslated region of the myostatin gene. In pigs, we recently showed that directional selection, operated by a BLUP animal model under a sib‐testing scheme, significantly changed, in quite a short period of time, allele frequencies of a few major genes in the Italian Large White breed (Fontanesi et al .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of directional selection on allele frequency changes have also been described in a few other livestock species. An interesting example was given by the Norwegian White Sheep breed for the myostatin 3 0 -UTR mutation causing muscle hypertrophia (Boman et al 2011). The introduction of BLUP-based breeding values and a classification system for carcass quality determined a rapid increase of the mutated allele in a short period of time without using any molecular genotyping (Boman et al 2011).…”
mentioning
confidence: 99%
“…An interesting example was given by the Norwegian White Sheep breed for the myostatin 3 0 -UTR mutation causing muscle hypertrophia (Boman et al 2011). The introduction of BLUP-based breeding values and a classification system for carcass quality determined a rapid increase of the mutated allele in a short period of time without using any molecular genotyping (Boman et al 2011). Similar changes were observed in the Italian Large White boars for a few gene markers that affect production traits, starting from the beginning of the selection scheme in this breed.…”
mentioning
confidence: 99%